Genius Loci : Exhibition. - Kovalciková, Mária (Zilina : Považská galéria umenia, 1991)
Bertolini, Michele ; Bod'a, Milos ; Brunovsky, Daniel ; Buhánová, Simona ; Cerný, Stano ; dickinger, Martin ; Galovský, Roman ; Gurioli, Giovanni ; Hosovský, Gabriel ; Hubert, Pierre - Alain ; Klammer, Richard ; Knut, Martin ; Krajco, Milan ; Krajcová, Daniela ; Mayertchak, Zdeno ; Novák, Milos ; Parini, Cristiano ; Pisár, Peter ; Sramka, Jozef ; Teren, Laco ; Wallner, Heimo
Genius Loci : Exhibition, Považská galéria umenia, Zilina, 16 August - 29 September 1991
Slovaaks & Engels
kunstcatalogus